A Study of Rate of Return and Risk of Investment in Stock Index Fund in Thailand and Foreign Countries: การศึกษาอัตราผลตอบแทนและความเสี่ยงของการลงทุน ในกองทุนรวมเลียนแบบดัชนีตราสารทุนของประเทศไทยและต่างประเทศ - Taweewat, Kanatnan (Journal of Applied Economics and Management Strategy, 2020)
บทคัดย่อ การศึกษาความครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาอัตราผลตอบแทนและความเสี่ยงเฉพาะตัวของการลงทุนในกองทุนรวมเลียนแบบดัชนีตราสารทุนของประเทศไทยและต่างประเทศ และ 2) สร้างกลุ่มสินทรัพย์ลงทุนที่มีประสิทธิภาพจากการลงทุนในกองทุนรวมเลียนแบบดัชนีตราสารทุนของประเทศไทยและต่างประเทศ โดยใช้ข้อมูลทุติยภูมิราคาหน่วยลงทุนย้อนหลังจากบริษัทหลักทรัพย์จัดการกองทุนไทยพาณิชย์ จำกัด ตั้งแต่วันที่ 4 มกราคม 2559 จนถึงวันที่ 3 มกราคม 2562 ซึ่งมีจำนวนทั้งสิ้น 489 ข้อมูล เพื่อนํามาใช้ในการคำนวณอัตราผลตอบแทนเฉลี่ย ความเสี่ยงเฉพาะตัว และค่าความแปรปรวนร่วมของแต่ละกองทุน แล้วนำมาคำนวณสัดส่วนการลงทุนในกองทุนรวมเลียนแบบดัชนีตราสารทุนของประเทศต่างๆ เพื่อสร้างกลุ่มสินทรัพย์ลงทุนที่มีประสิทธิภาพผลการศึกษาพบว่ากองทุน SCBNK225 มีอัตราผลตอบแทนเฉลี่ยสูงที่สุดอยู่ที่ร้อยละ 16.08 รองลงมาคือ SCBCEH SCBKEQTG SCBSET และ SCBINDIA มีอัตราผลตอบแทนเฉลี่ยอยู่ที่ร้อยละ 14.68 ร้อยละ 14.15 ร้อยละ 12.58 และร้อยละ 11.35 ตามลำดับ ส่วนกองทุนที่มีความเสี่ยงต่ำที่สุดคือ SCBSET มีค่าส่วนเบี่ยงเบนมาตรฐานอยู่ที่ร้อยละ 7.40 รองลงมาคือ SCBNK225 SCBINDIA SCBCEH และ SCBKEQTG มีค่าส่วนเบี่ยงเบนมาตรฐานเท่ากับร้อยละ 8.36 ร้อยละ 11.21 ร้อยละ 12.70 และร้อยละ 17.58 ตามลำดับ โดยกองทุน SCBSET และ SCBNK225 มีค่าความแปรปรวนร่วมต่ำที่สุดอยู่ที่ 0.0035 ดังนั้นจึงสามารถสร้างกลุ่มหลักทรัพย์ลงทุนที่มีประสิทธิภาพได้จากการแบ่งสัดส่วนการลงทุนในกองทุน SCBSET และ SCBNK225 แล้วจะทำให้ความเสี่ยงจากการลงทุนต่ำลงได้ โดยที่ยังคงได้รับอัตราผลตอบแทนมากกว่าหรือเท่ากับการลงทุนเพียงกองทุนเดียว ยกเว้นกรณีที่นักลงทุนต้องการอัตราผลตอบแทนเฉลี่ยจากการลงทุนสูงที่สุด นักลงทุนจะไม่สามารถสร้างกลุ่มหลักทรัพย์ใหม่ได้ แต่จะต้องนำเงินทั้งหมดไปลงทุนในกองทุนที่มีอัตราผลตอบแทนเฉลี่ยสูงที่สุดเพียงกองทุนเดียว ABSTRACT This study aimed to 1) calculate rate of return and stand-alone risk of investment in stock index fund in Thailand and foreign countries and 2) identity alternative portfolio for more efficient investment in stock index fund in Thailand and foreign countries. The study utilized secondary data of net asset value per unit obtained from SCB Asset Management Co. Ltd. from January 4th, 2013 up to January 3rd , 2019 which came out with 489 figures. From these data, average rate of return, stand-alone risk and covariance of each stock index fund were computed. These outcomes led to the calculation to identify appropriate portfolio for more efficient investment in stock index fund in various countries. The study revealed that, out of stock index funds under this study, SCBNK225 yielded the highest average rate of return at 16.08 percent followed by SCBCEH, SCBKEQTG, SCBSET and SCBIDIA with the figures of 14.68, 14.15, 12.58 and 11.35 percent respectively. The stock index fund with the lowest risk was SCBSET which had standard deviation of 7.40 percent followed by SCBNK225, SCBINDIA, SCBCEH and SCBKEQTG standard deviation of 8.36, 11.21, 12.70 and 17.58 percent respectively. Since SCBSET and SCBNK225 had the lowest covariance at 0.0035, investor could set up more efficient portfolio by diverting his single fund investment proportionally in SCBSET and SCBNK225 in order to help reducing his risk of investment and still receiving the same or even higher rate of return as of single fund investment. The only exceptional case occurred when investor wanted the highest average rate of return, he could not set up better portfolio since he had to put all his investment in the stock index fund with the highest average rate of return.